Studi Literatur : Pengaruh Manajemen Laba dan Good Corporate Governance (GCG) terhadap Pelaporan Kecurangan Keuangan (Fraud) - Muhamad Nuralamsah; Aris Eddy Sarwono (Pusat Riset dan Inovasi Nasional, 2025)
Contemporary business landscapes require openness and responsibility in financial disclosure; however, profit manipulation activities and inadequate corporate governance mechanisms frequently lead to concealed financial misconduct. This systematic review investigates how profit management and governance implementation affect hidden financial irregularities, emphasizing current scholarly works from recent years. Through comprehensive document examination methodology, this research assesses scholarly publications, corporate reports, regulatory frameworks, and pertinent case analyses from repositories such as ScienceDirect, JSTOR, Google Scholar, and Sinta covering the 2019-2024 timeframe. Results demonstrate intricate connections whereby profit management may serve as a regulatory mechanism to minimize fraudulent behaviors when applied appropriately, while governance efficacy is significantly influenced by execution standards. Institutional shareholding and oversight committees demonstrate success in constraining manipulative activities, while alternative formal mechanisms such as independent board members exhibit variable effectiveness. Results suggest that established governance frameworks are inadequate without proper execution, sufficient personnel expertise, and robust corporate culture. This investigation offers important perspectives for policymakers and industry professionals concerning financial misconduct patterns and mitigation approaches